Lévinas, Filósofo Judío (2012)
Lévinas’philosophy is inspired by the traditional sources of Judaism, although thesehardly surface in his discourse. It is convenient to consider his work as apalimpsest withtwo textual levels, the explicit level (philosophicalphenotext) and the hidden level (Juif prototext). The Other and the Same are related to each other according to the biblical linkmodel YHWH-Israel: Revelation inspires epiphany of visage while Redemption underlies subjectivity reconstruction in ethical terms. In philosophy, Lévinasian Heterology reiteratesthe central experiences of Hebrew monotheism. Key words: Ethics, Judaism, palimpsest, Revelation, Redemption, visage, substitution.